SISTEM PENDIDIKAN YANG DITERAPKAN OLEH JEPANG DI INDONESIA - ALINUR . (LP2MTBM MAKARIOZ, 2020)
This research aimed to describe what has been done by the men especially the students for the period of Japan’s occupation which means there’s so much struggle that has been done to achieve Indonesia’s independence. On the period of Japan’s occupation, Japan’s military government has full power to organize in almost every sector such as social’s sector, government, military, economic and education.